PENERAPAN SUPERVISI KUNJUNGAN KELAS UNTUK MENINGKATKAN KINERJA GURU SEKOLAH DASAR NEGERI - Danurwati, Suprih; Slameto, Slameto (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study aimed to know that the implementation of classroom visit supervision can improve the performance of teachers SD Negeri 2 Kalimanggis in learning management. Subjects in this study were teachers at the SD Negeri 2 Kalimanggis, Kaloran District, Temanggung. The procedure used in this study consisted of three series of activities that will be carried in repeating cycles, include (a) planning, (b) the action by observation, and (c) reflection. The research approach used action research methods, while the data collection used study of documentation, observation, questionnaires and interviews. The results showed an increased ability of teachers to prepare lesson plans and manage the learning of the first, second, to the third action. The conclusion was the classroom visit supervision can improve the performance of teachers at SDN 2 Kalimanggis in learning management. Suggestions given to teacher was need to utilize the supervision activities as a source of information to improve teachers competence and performance. For the school principle need to utilize the result of this study as a reference in conducting research, while for school supervisor also need to utilize the results of this study as one of the references in the activities guidance towards principal and teachers in improving their performance.